2008
DOI: 10.1017/s0266467408005415
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of nearctic–neotropical songbird migrants in a forest restoration site in southern Costa Rica

Abstract: Many ecological relationships that are inherently reciprocal are often studied from one perspective only (Agrawal et al. 2007). One example is the interaction between tropical forests and nearctic-neotropical migratory songbirds (hereafter migrants). Several studies have determined that some migrant populations are limited by conditions at their tropical wintering grounds in Central America, South America and the Caribbean (Marra et al. 1998, Mills 2006); however, the ecological role of migrants in these tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Additional research demonstrated that mixed-species tree plantations both attracted seed dispersers and improved conditions for seed germination and seedling survival [35][40]. Seed dispersal trends were driven by small omnivores [41], [42], and the effects of tree planting varied by feeding guild [24], [26], [43] and habitat associations [44], [45].…”
Section: Introductionmentioning
confidence: 99%
“…Additional research demonstrated that mixed-species tree plantations both attracted seed dispersers and improved conditions for seed germination and seedling survival [35][40]. Seed dispersal trends were driven by small omnivores [41], [42], and the effects of tree planting varied by feeding guild [24], [26], [43] and habitat associations [44], [45].…”
Section: Introductionmentioning
confidence: 99%
“…We may infer that scale-dependent processes (forest patches at the local scale, and movements through the landscape at the regional scale) should be interconnected and interdependent in order to conserve and increase forest areas. Recent studies have highlighted the importance of migratory species for the forest-restoration process (Leighton Reid et al 2008;Lindell et al 2012, among others).…”
Section: Introductionmentioning
confidence: 99%
“…2009) and foraging behavior (Morrison et al . 2010, Morrison & Lindell 2011), but few tropical studies have assessed bird habitat preference at a community level across different restoration treatments (reviewed by Ruiz‐Jaen & Aide 2005, Aerts et al . 2008, Lindell 2008, Reid et al .…”
mentioning
confidence: 99%
“…We found no significant correlations between these structural variables (Spearman's ρ , α =0.05). While distance to old growth forest has been an important explanatory variable for bird community assemblage in some studies ( e.g ., Neilan et al . 2006, Reid et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation